A sandwich-structured Nb/NiTi composite with good bio-compatibility, near-linear-elastic deformation and large elastic admissible strain. (15th February 2021) - Guo, Shun; Zhang, Huihui; Chen, Yueliang; Liu, Qing; Wu, Ruitang; Ma, Wen; Liu, Haixia; Meng, Qingkun; Liu, Guanglei; Cheng, Xiaonong; Zhao, Xinqing
Abstract: A combination of good bio-compatibility and large near-linear-elastic deformability was achieved in a novel sandwich-structured Nb/NiTi composite. This Nb/NiTi composite comprises of exterior β-phase Nb layers and interior NiTi layer containing the (001) compound twined B19′-martensite and trace amount of B2-parent phase. The exterior nontoxic Nb layers offer the good bio-compatibility for Nb/NiTi composite by isolating the surface of the interior NiTi layer from cells. In situ synchrotron X-ray diffraction measurement reveals that besides the intrinsic elastic deformation, a slight and recoverable B2↔B19′ stress-induced martensitic (SIM) transformation occurs in a continuous mode, which produces the extra phase transformation strain and thus contributes to the large elastic admissible strain of the Nb/NiTi composite. The large near-linear-elastic deformability in the Nb/NiTi composite is mainly due to the intrinsic elasticity, the recoverable SIM transformation proceeding in a continuous mode as well as the (001) compound twins within B19′ martensite. These results may contribute to design and develop novel biomedical composites that have good bio-compatibility and large near-linear-elastic deformability. Highlights: A novel Nb/NiTi composite with a sandwich structure was designed. It can exhibit good bio-compatibility and large near-linear elasticity. The mechanisms of the large near-linear elasticity were elucidated.